Principles of hormone behavior relations - Pfaff, Donald W., 1939-; Phillips, M. Ian.; Rubin, Robert Terry; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier Academic Press, 2004)
This text introduces underlying principles of the endocrine regulation of behavior in animals and humans. Every chapter begins by stating a principle, followed by specific examples of hormone actions derived from scientific experiments and clinical observations, and concludes with a few challenging unanswered questions. The reference source Hormones, Brain & Behavior identified this field as rapidly expanding within neurobiology and endocrinology. Now, this well-illustrated and referenced text will serve students from undergraduate school to medical school as they learn this new discipline. * Uniform presentation of material across all chapter, with each chapter addressing a key principle, illustrated by basic experimental and clinical examples * Includes user-friendly features such as boxed figures with extended captions and references, numerous clinical notes, and a comprehensive list of abbreviations * Illustrations highlight both the clinical and basic science information.
Characterizing the Phenomena: Hormone Effects are Strong and Reliable -- History: Hormone Effects can Depend on Family, Gender, and Development -- Time: Hormonal Effects on Behavior Depend on Temporal Parameters -- Space: Spatial Aspects of Hormone Administration and Impact are Important -- Mechanisms: Molecular and Biophysical Mechanisms of Hormone Actions Give Clues to Future Therapeutic Strategies -- Environment: Environmental Variables Influence Hormone/Behavior Relations -- Evolution.
Includes bibliographical references (pages 295-322) and index.
Print version record.
Elsevier
Keywords: Hormones -- Health aspects; Hormones -- Physiological effect; Hormones -- Psychological aspects; Hormones -- Research; Human behavior; Hormones -- Aspect sanitaire; Hormones -- Aspect physiologique; Hormones -- Aspect psychologique; Hormones -- Recherche; Comportement humain; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Hormonen; Gedrag; Endocrinologie; Behavior -- physiology; Hormones -- metabolism; Hormones -- physiology; Brain Chemistry -- physiology; Psychophysiology; Hormones -- Physiological effect; Hormones -- Psychological aspects; Hormones -- Research; Human behavior; Electronic books